Spoilage potential of brettanomyces bruxellensis strains isolated from Italian wines. (March 2018) - Guzzon, Raffaele; Larcher, Roberto; Guarcello, Rosa; Francesca, Nicola; Settanni, Luca; Moschetti, Giancarlo
Abstract: Brettanomyces bruxellensis is an important wine spoilage agent. In this study a population of Brettanomyces strains isolated from Italian wines was thoroughly investigated to evaluate adaptability to wine conditions and spoilage potential. The presumptive isolates of Brettanomyces were identified at species level with 26S rRNA gene sequencing and species-specific PCR, and subsequently subjected to analysis of intra-species variability through the study of intron splice sites (ISS-PCR). Although, some strains were tracked in wines from different regions, extensive genetic biodiversity was observed within the B . bruxellensis population investigated. All strains were evaluated for their growth ability in the presence of ethanol, high sugar content, low pH, different temperatures and sulphur dioxide, using optical density and flow cytometry measurement. The ability of yeasts to produce ethyl phenols in red wines with different chemical compositions was evaluated by means of high performance liquid chromatography with electrochemical detection (HPLC-ECD). The results highlighted wide variability in B . bruxellensis in response to wine limiting factors and in terms of the accumulation of ethyl phenols. As regards this last aspect, the differences found among strains were closely related to chemical composition of wine and strain resistance to environmental stress factors, making a priori evaluation of risk of wine alteration quite difficult. These results suggest that strategies for the control of Brettanomyces should be tailored on the basis of strain distribution and wine characteristics. Graphical abstract: Highlights: The spoilage potential of a collection of B . bruxellensis strains was investigated. Genotyping and tolerance to stress growth factors revealed large strain variability. The accumulation of volatile phenols was evaluated in wines with different chemical composition. The accumulation of ethyl phenols depends on yeast strains and the characteristics of wines.